2018
DOI: 10.1051/e3sconf/20187201007
|View full text |Cite
|
Sign up to set email alerts
|

Review of Icing Effects on Wind Turbine in Cold Regions

Abstract: This paper describes a brief overview of main issues related to atmospheric ice accretion on wind turbines installed in cold climate region. Icing has significant effects on wind turbine performance particularly from aerodynamic and structural integrity perspective, as ice accumulates mainly on the leading edge of the blades that change its aerodynamic profile shape and effects its structural dynamics due to added mass effects of ice. This research aims to provide an overview and develop further understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…The IR images are processed to detect ice by evaluating each profile surface temperature, which helped in identifying the ice distribution patterns and locations along each profile surface. In previous study (Afzal and Virk, 2018;Ghani and Virk, 2013;Hudecz, 2014;Mohseni et al, 2012), results show that ice mainly accretes along leading edge, therefore, five different locations (as line) are marked along leading edge area of each profile during image processing for analysis of surface temperature variation. These locations are shown in Figure 3.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The IR images are processed to detect ice by evaluating each profile surface temperature, which helped in identifying the ice distribution patterns and locations along each profile surface. In previous study (Afzal and Virk, 2018;Ghani and Virk, 2013;Hudecz, 2014;Mohseni et al, 2012), results show that ice mainly accretes along leading edge, therefore, five different locations (as line) are marked along leading edge area of each profile during image processing for analysis of surface temperature variation. These locations are shown in Figure 3.…”
Section: Results and Analysismentioning
confidence: 99%
“…Similarly, in recent years due to increased energy demands in high north, icing on wind turbine blades has got attention as it affects blade aerodynamics that lead to decrease in annual power production and can pose a safety risk due to ice shedding (Tammelin et al, 2000). Atmospheric ice accretion on wind turbine mainly occurs due to the impingement of super-cooled water droplets that freeze on blade surface (Afzal and Virk, 2018). The distribution of ice loads along blade surface is not constant due to change in airflow behaviour and geometric characteristics of the blade from root to tIp section.…”
Section: Introductionmentioning
confidence: 99%
“…It is concentrated more precisely at the tip of the blade. Icing is responsible for the deterioration of the geometry due to the accumulation of ice which produces small fissures and premature delamination in the material of the wind turbine (Afzal and Virk, 2018).…”
Section: Structural Performances Analysismentioning
confidence: 99%
“…The authors also indicated that an increase in blade mass caused by icing reduced its natural frequencies, and that symmetrical icing of all three blades decreased the loads acting on the turbine components, while asymmetrical icing caused loads and vibrations in the structure. Afzal and Virk (2018) had shown that the additional mass of ice located on the leading edge of the blade has important effects on the efficiency of wind turbines. Ice formation on the surface of the wind turbine blades is not homogeneous along the entire length of the blade, it causes more loads and increase the excitation of edgewise vibrations.…”
Section: Introductionmentioning
confidence: 99%